Efficacy of motivational interviewing and cognitive behavioral therapy for anxiety and depression symptoms following traumatic brain injury. Issue 5 (28th December 2015) - Ponsford, J.; Lee, N. K.; Wong, D.; McKay, A.; Haines, K.; Alway, Y.; Downing, M.; Furtado, C.; O'Donnell, M. L.
Abstract : Background: Anxiety and depression are common following traumatic brain injury (TBI), often co-occurring. This study evaluated the efficacy of a 9-week cognitive behavioral therapy (CBT) program in reducing anxiety and depression and whether a three-session motivational interviewing (MI) preparatory intervention increased treatment response. Method: A randomized parallel three-group design was employed. Following diagnosis of anxiety and/or depression using the Structured Clinical Interview for DSM-IV, 75 participants with mild-severe TBI (mean age 42.2 years, mean post-traumatic amnesia 22 days) were randomly assigned to an Adapted CBT group: (1) MI + CBT ( n = 26), or (2) non-directive counseling (NDC) + CBT ( n = 26); or a (3) waitlist control (WC, n = 23) group. Groups did not differ in baseline demographics, injury severity, anxiety or depression. MI and CBT interventions were guided by manuals adapted for individuals with TBI. Three CBT booster sessions were provided at week 21 to intervention groups. Results: Using intention-to-treat analyses, random-effects regressions controlling for baseline scores revealed that Adapted CBT groups (MI + CBT and NDC + CBT) showed significantly greater reduction in anxiety on the Hospital Anxiety and Depression Scale [95% confidence interval (CI) −2.07 to −0.06] and depression on the Depression Anxiety and Stress Scale (95% CI −5.61 to −0.12) (primary outcomes), and greater gains in psychosocial functioning on Sydney Psychosocial Reintegration Scale (95% CI 0.04–3.69) (secondary outcome) over 30 weeks post-baseline relative to WC. The group receiving MI + CBT did not show greater gains than the group receiving NDC + CBT. Conclusions: Findings suggest that modified CBT with booster sessions over extended periods may alleviate anxiety and depression following TBI.